Penguatan Kapasitas UMKM Angkringan Melalui Pendampingan Manajemen Usaha dan Transformasi Digital - Nora Listiana; Suci Ayu Sudari; Alfath Disya Arryansyah; Muhammad Fajar Ramadhani; Rasya Aditya Nanda (Eastasouth Journal of Positive Community Services, 2026)
This Community Service (Abdimas) activity aims to increase the capacity of angkringan (angkringan-friendly) MSMEs through business management and digital marketing assistance. Partners' challenges include limited promotional strategies, rudimentary business management, and minimal use of digital technology. Implementation methods include observation, interviews, training, and direct mentoring. Activities focus on strengthening business concepts, menu innovation, improving service quality, and utilizing social media and digital payment systems. Results demonstrate an increase in partners' understanding of business management and marketing, thereby enhancing the competitiveness and sustainability of angkringan-friendly MSMEs.